2021
DOI: 10.3390/healthcare9111495
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with SARS-CoV-2 Infection Risk among Healthcare Workers of an Italian University Hospital

Abstract: We report the results of a study on the cumulative incidence of SARS-CoV-2 infections in about 6000 workers of the University Hospital of Modena, Northern Italy, in the period March 2020–January 2021, and the relations with some individual and occupational factors. Overall, in healthcare workers (HCW) the cumulative incidence of COVID-19 during the period was 13.8%. Results confirm the role of overweight and obesity as significant risk factors for SARS-CoV-2 infection. Chronic respiratory diseases, including a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…The number of tests performed varied according to the occupational role profile, which is in line with the results reported by Modenese and colleagues [57] and Jones and colleagues [64]. HCWs were enrolled in a voluntary testing program with a flexible follow-up schedule, which led to different attendance frequencies.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The number of tests performed varied according to the occupational role profile, which is in line with the results reported by Modenese and colleagues [57] and Jones and colleagues [64]. HCWs were enrolled in a voluntary testing program with a flexible follow-up schedule, which led to different attendance frequencies.…”
Section: Discussionsupporting
confidence: 79%
“…One possible explanation for this observation is that their contacts with patients and coworkers were less close and briefer than those of nurses and paramedics. During the pandemic, physician-patient interactions were rethought and reorganized in order to limit close contact as much as possible [57].…”
Section: Discussionmentioning
confidence: 99%
“…These factors are: (i) older age; (ii) the number of underlying medical conditions, including (but not limited to) cancer, chronic kidney disease, liver disease, chronic respiratory diseases, various neurological conditions, diabetes, cardiovascular diseases including hypertension and various others; (iii) long-standing systemic health and social inequities, certain ethnic minority groups and disabilities; (iv) a smoking habit; (v) pregnancy; (vi) refusal of, or contraindication to undergo, anti-COVID-19 vaccination; (vii) inadequate compliance with the preventive measures for COVID-19 [ 12 ]. Considering the diseases, certainly those of them directly affecting the immune response and causing immunodeficiency (e.g., HIV infection, lymphoproliferative and immunological diseases and others) or those conditions requiring chronic immunosuppressive therapy (e.g., use of antiblastic drugs, radiotherapy, prolonged use of corticosteroids and others) can both have an influence on the antibody titer [ 12 , 13 , 14 ]. Another factor of interest from an occupational health point of view for healthcare workers and other professions is the performance of nightshifts at work.…”
Section: Introductionmentioning
confidence: 99%
“…Another factor of interest from an occupational health point of view for healthcare workers and other professions is the performance of nightshifts at work. This is a recognized work-related risk factor, possibly involved in the dysregulation of the circadian rhythm with repercussions also for the immune function [ 13 , 15 ]. Considering the relation with SARS-CoV-2 infection, it has been reported that nightshift healthcare workers during the pandemic had a higher job demand, longer working hours and poorer sleep quality, therefore increasing the occasions for contagion [ 13 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The highest seroprevalence was observed among nurses and assistant nurses with more than two times higher than janitors and also higher than physicians, which could be due to closer contact with patients infected with COVID-19 ( 4 ). A study in Italy found a triple odds of positive serology among nurses and nurse assistants compared to non-HCWs ( 16 ). Similarly a systematic review on 49 similar studies reported higher seropositivity in HCWs working in COVID-19 patient wards, direct work with patients, front lines, and health care assistants ( 17 ).…”
Section: Discussionmentioning
confidence: 99%